STUDENT â TEACHER INTERACTION: A CASE OF THE SECOND YEAR OF STATE SENIOR HIGH SCHOOLS IN CEPU - Ari Wibowo, Andika Cahya (VISION, 2014)
Abstract The purposes of the study are to Dnd out the amount of lan- guage produced by the teacher (Teacher Talking Time) and by the students (Student Talking Time) and to identify the characteristics of the classroom interaction in the Senior High School English classes. The study involved the second year students and the English teachers of SMA N I Cepu and SMA N II Cepu as the object of the study. Observation method is utilized in the study to collect the data. The study is supported by one thousand four hundreds and forty data which are categorized into the ten categories of Flanders (FIAC). In details, the Drst result of the analysis shows that 70.5 % of the classroom available time was taken by the teacher and the stu- dents only took 21.6 % of the available time during the interaction in SMA N I Cepu. Meanwhile, during the interaction in SMA N II Cepu the teacher took 69.6 % of the classroom available time while the students only took 22.2 % of the available time. The second result shows that the dominant characteristic of the classroom interaction in SMA N I Cepu was Teacher Talking Time while the dominant characteristic in SMA N II Cepu was Con- tent Cross. Keywords : Classroom Interaction, Flanders Interaction Analyze Categories (FIAC), Teacher Talking Time, Student Talking Time, The Characteristics of Classroom Interaction